2020
DOI: 10.3847/1538-3881/ab9b84
|View full text |Cite
|
Sign up to set email alerts
|

Two Intermediate-mass Transiting Brown Dwarfs from the TESS Mission

Abstract: We report the discovery of two intermediate-mass transiting brown dwarfs (BDs), TOI-569b and TOI-1406b, from NASA's Transiting Exoplanet Survey Satellite mission. TOI-569b has an orbital period of P=6.55604±0.00016 days, a mass of M b = 64.1±1.9 M J , and a radius of R b = 0.75±0.02 R J. Its host star, TOI-569, has a mass of M å = 1.21±0.05 M  , a radius of R å = 1.47±0.03 R  , = +  Fe H 0.29 0.09 [ ] dex, and an effective temperature of T eff = 5768±110K. TOI-1406b has an orbital period of P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 93 publications
2
24
0
Order By: Relevance
“…Fig. 4 shows the mass-radius relation for the known 23 brown dwarfs transiting main-sequence stars (Carmichael et al 2020), as well as the three brown dwarfs that eclipse their white dwarf primaries. NLTT5306B is shown assuming it has a radius of its Roche lobe (in reality, it may of course be smaller than this).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 4 shows the mass-radius relation for the known 23 brown dwarfs transiting main-sequence stars (Carmichael et al 2020), as well as the three brown dwarfs that eclipse their white dwarf primaries. NLTT5306B is shown assuming it has a radius of its Roche lobe (in reality, it may of course be smaller than this).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4. Mass-radius relation for the 23 known brown dwarfs transiting main-sequence stars(Carmichael et al 2020 and references therein). The three known brown dwarfs that eclipse white dwarfs(Littlefair et al 2014;Parsons et al 2017;Casewell et al 2020) are also shown plotted with filled squares.…”
mentioning
confidence: 99%
“…Space-based photometric missions are ideal to find these rare objects given their robust photometric precision and long uninterrupted observations, and recent missions such as Kepler (Borucki et al 2010) and K2 (Howell et al 2014) have led to successful follow-up mass measurements of transiting brown dwarfs (e.g., Bayliss et al 2017;Cañas et al 2018;Carmichael et al 2019;Persson et al 2019). The currently operating space-based all-sky Transiting Exoplanet Survey Satellite (TESS; Ricker et al 2015) has continued to populate the sparse desert with well-characterized brown dwarfs and very low-mass stars (e.g., Šubjak et al 2020;Carmichael et al 2020Carmichael et al , 2021Mireles et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent discoveries by TESS shows that substellar objects do span the entire mass-range (Carmichael et al 2020).…”
Section: Introductionmentioning
confidence: 99%